The cushioning function of woodpecker's jaw apparatus during the pecking process. Issue 5 (6th July 2021) - Xu, Peng; Ni, Yikun; Lu, Shan; Liu, Sijian; Zhou, Xue; Fan, Yubo
Abstract: Woodpeckers can withstand a fierce impact during pecking without any brain injury. Although directly involved in the whole pecking, the role of the jaw apparatus played in the impact-resistant process of woodpeckers is still not fully clear. We employed finite element analysis, impact tests in vivo, and post-traumatic brain anatomical observation to evaluate the protective function of the jaw apparatus. Forehead impact model and beaks impact without quadrate joints model were selected as control groups. The maximum impact force, the maximum stress of skull, the maximum strain and strain rate of brain were employed as the main parameters for comparison. The simulations showed that: the impact force, the skull's maximum von Mises stress, the brain's maximum principal strain and the principal strain rate increased by 72%, 24%, 148% and 106%, when the forehead rather than beaks were impacted; while they increased by 23%, 74%, 116% and 72% in the beaks impact without quadrate joints model. The results of simulations were supported by the anatomical observation: brain injury was not found after beak impact tests; serious hyperaemia, bleeding, and contra-coup injury were observed after forehead impact tests. This study discovered that the jaw apparatus acted as a cushion during the pecking process and the quadrate bone and joints changed the type of load and prolonged the acting time, which reduced the impact load acted on the skull and brain. This study would provide new inspirations to develop the device for brain protection, bio-inspired structure and material for energy-absorbing.